PRELIMINARY RESEARCH ON 7E LEARNING CYCLE MODEL-BASED MODULE DEVELOPMENT OF THE INTEGRATED TECHNOLOGICAL KNOWLEDGE - Dea Mustika; Laili Rahmi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper describes data from the preliminary research stage, which will be used as a basis for the development of an Elementary Natural Science Learning module based on the learning cycle 7e model integrated with technological knowledge. The development model used is the Plomp model, which is mainly focused on the preliminary research stage. Data collection instruments are interviews, questionnaires, and observation. The research subjects involved two lecturers and 51 students who took Elementary Natural Science Learning courses. The preliminary research that was carried out included the analysis of RPS, analysis of problems and lecturer’s needs, and analysis of problems and students’ needs. The results of the research indicate that based on 9 materials for Elementary Natural Science learning subjects, it was still found problems with learning resources, learning implementation, and teaching materials. In addition, 100% of lecturers’ and students’ responses dealt with developing teaching modules for Elementary Natural Science Learning courses. The research conclusion implies that the results of the preliminaryresearch can be used as a basis for the development of an Elementary Natural Science module based on the learning cycle 7e model integrated with technological knowledge.